2020
DOI: 10.1371/journal.pone.0229604
|View full text |Cite
|
Sign up to set email alerts
|

Long rallies and next rally performances in elite men’s and women’s badminton

Abstract: The aim of the present study was twofold: (i) to identify contextual variables associated with the occurrence of long rallies while investigating time-related and technical parameters; and (ii) to identify performance differences between long rallies and the subsequent rally when accounting for match-context and the players' sex. The sample included 60 men's (n = 4,475 rallies) and 60 women's (n = 4,490 rallies) matches randomly selected from the 2015 World Badminton Super Series and World Championship (the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 14 publications
(38 reference statements)
1
16
0
1
Order By: Relevance
“…Furthermore, all subjects were fitted with a heart rate monitoring system Polar H10 Polar Electro Oy, Finland), and asked to perform a fatigue test on a treadmill. The warm-up session had a starting speed of 8 km•h−1, which continued to 10 km•h−1, and increased by two km•h−1 every 3 min (14,20). The test ended when the subjects were exhausted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, all subjects were fitted with a heart rate monitoring system Polar H10 Polar Electro Oy, Finland), and asked to perform a fatigue test on a treadmill. The warm-up session had a starting speed of 8 km•h−1, which continued to 10 km•h−1, and increased by two km•h−1 every 3 min (14,20). The test ended when the subjects were exhausted.…”
Section: Methodsmentioning
confidence: 99%
“…Muscle fatigue is generally defined as the reduced ability of a person to generate adequate power due to the chain of events cut off from the central nervous system to the muscle fibers (20). This overall feeling of tiredness is classified into peripheral and central fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…Results of these studies showed that the scaling of equipment and playing area improve the players’ match performance, engagement, enjoyment and the development of desirable movement patterns related to motor variability. However, in badminton, the research has focused to analyze the following aspects: technical and tactical [ 30 ], physiological [ 31 , 32 ] or performance analysis [ 33 , 34 , 35 , 36 ] in elite and junior elite players, and not so much in scaling the equipment and play space for junior players. Although, some associations and federations, such as the Spanish Badminton Federation [ 37 ], in a similar way to the tennis 10’s program developed by the International Tennis Federation, do structure badminton competitions for junior players, to manipulate key task constraints.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, other studies have focused their attention on understanding the differences between these parameters when considering the context, such as gender, modalities, or situational variables (number of sets, intervals of play, quality of opponent, etc.) [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, most of the badminton literature has focused on predicting winning and losing players using key performance indicators, such as the type of service, the type of stroke, or the temporal parameters [ 1 , 3 , 5 , 6 ]. However, the spatial-related variables were not addressed to identify how the space of play (where each player hits the shuttlecock) was used during badminton matches, and then how these complex behaviors may identify badminton performance profiles.…”
Section: Introductionmentioning
confidence: 99%